DETERMINATION OF OPTIMUM MAINTENANCE INTERV AL IN TERMS OF COST - Chowdhury, Ch. (Periodica Polytechnica Mechanical Engineering, 1987)
If a system can be characterized by an increasing failure rate, then it is advisable to replace it before it has aged too greatly. On the other hand frequent replacement means excessive cost. Therefore, the optimum replacement interval has to be determined which will minimize the maintenance cost. Here a simple method has been worked out to ascertain the optimum value of block replacement interval. An error committed in reference (1), while calculating the value of renewal density has been rectified. A necessary condition for calculating the optimum block interval is derived.